\(\left(\frac{2}{\sqrt{7}-\sqrt{5}}-\frac{3}{\sqrt{7}+\sqrt{5}}\right)\left(5\sq...">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

3 tháng 8 2021

 \(\sqrt{46}\)nha

3 tháng 8 2021

\(\left(\frac{2}{\sqrt{7}-\sqrt{5}}-\frac{3}{\sqrt{7}+\sqrt{5}}\right)\left(5\sqrt{5}+\sqrt{7}\right)\)

\(=\left(\frac{2\sqrt{7}+2\sqrt{5}-3\sqrt{7}+3\sqrt{5}}{2}\right)\left(5\sqrt{5}+\sqrt{7}\right)\)

\(=\left(\frac{-\sqrt{7}+5\sqrt{5}}{2}\right)\left(5\sqrt{5}+\sqrt{7}\right)=\frac{25.5-7}{2}=\frac{118}{2}=59\)

23 tháng 8 2017

mik làm bài này

linh tinh

bn ơi

cho mik

xin 1 L-I-K-E

b,  
 
 
 
 

d, 
 
 
 
 
 
 
 
 
 

22 tháng 8 2017

\(\sqrt{\frac{4}{\left(2-\sqrt{5}\right)^2}}-\sqrt{\frac{4}{\left(2+\sqrt{5}\right)^2}}\)

\(=\frac{2}{\sqrt{5}-2}-\frac{2}{2+\sqrt{5}}\)

 \(=\frac{2\left(\sqrt{5}+2\right)-2\left(\sqrt{5}-2\right)}{5-4}\)

\(=2\sqrt{5}+4-2\sqrt{5}+4\)

\(=8\)

28 tháng 8 2017

1. 

= -(13 + 3 căn7 ) / 2  +  -(7 + 3 căn7 ) / 2 

=  -7 + 3 căn7